150 REAL-TIME HIGH-RESOLUTION COMPARISON OF TRACHEAL AND BRONCHIAL INJURY CHANGES DURING SMOKE INHALATION IN RABBITS USING OPTICAL COHERENCE TOMOGRAPHY. Issue 1 (1st January 2007) - Tran, A.; Ju, J.; Uppal, A.; Tseng, L.; Kreuter, K.; Mukai, D.; Guo, S.; Burney, T.; Chen, Z.; Mahon, S.; Brenner, M.
Abstract : Background: Smoke inhalation injury causes acute airway swelling that results in significant morbidity and mortality. There are currently no available modalities for early detection of this edema. We performed high-resolution endobronchial optical coherence tomography (OCT) using a prototype SLD-OCT system and flexible fiberoptic probes we constructed to obtain novel real-time images of inhalation at near histologic levels showing differences between tracheal and bronchial responses to smoke in vivo. Method: Nineteen New Zealand rabbits (four controls, seven tracheal, and eight bronchial) were intubated and mechanically ventilated. The experimental group was exposed to inhaled smoke. The OCT probe was introduced through the endotracheal tube. Images of airway mucosa and submucosa were obtained at baseline and at set time intervals. The mucosal and submucosal thickness was measured and compared between the three groups. The images were also compared to histologic sections of the trachea. Results: Starting at 30 minutes after smoke inhalation, there was significant bronchial airway thickening. This was maintained through 360 minutes. No significant tracheal thickening was detected. Conclusions: OCT is capable of detecting changes in airway swelling following inhalation injury and may be very useful for inhalation injury assessment. Significant differences were seen between bronchial and tracheal effects of acute smoking inhalation. Further studies will be needed to determine the causes for these differences.